Numerical study on the lubrication in total knee replacements: The influence of dynamics, geometry, material and fluid - Marian, Max; Rothammer, Benedict; Bartz, Marcel; Nečas, David; Vrbka, Martin; Wimmer, Markus A; Wartzack, Sandro (7th World Tribology Congress, WTC 2022, 2022)
For an adequate design of total knee replacements, knowledge about stresses and lubrication conditions is vital. Within this study, a numerical model is presented and validated with experimental data. Good agreement between model predictions and experimental data as well as a strong influence of fluid, material and geometry assumptions as well as transient effects were found. It was demonstrated that the rheological synovial fluid properties have a decisive impact on the tribological behavio
Keywords: Total knee replacement; Synovial joint tribology; Soft-elastohydrodynamic lubrication; Finite Element Method